GENETIC FACTORS INFLUENCING THE EFFECTIVENESS AND SAFETY OF LONG-TERM ANTICOAGULANT THERAPY - T. V. Burkova; I. A. Goncharova (Кардиоваскулярная терапия и профилактика)
Late postoperative thrombotic and haemorrhagic complications in anticoagulant-treated patients remain one of the key problems of the modern clinical medicine. At present, the most widely used anticoagulant is warfarin, a vitamin K antagonist. One of the reasons for a pathological reaction to the therapeutic concentration of warfarin could be individual features of warfarin metabolism, determined by relevant genes. The literature data suggest that protein-coding CYP2C9 and VKORC1 genes play an important role in the development of postoperative complications. However, the individual warfarin dosage can be influenced by a wide range of other genetic polymorphisms.